Gênesis 2,4b-25: uma análise literária, histórica e antropológica. - Silva, Alex Antonio da (2019)
Among the various fields of interest in theological studies, biblical research, conducted through various exegetical methods, is among the most important. Through the bibliographical research, the present work lends itself to a literary, historical and anthropological analysis of the narrative of the creation of man and woman in Gn 2,4b-25. Once the Bible appears as a literary work, the first work to be carried out consists in highlighting the literary aspects of the chosen period. Next comes the presentation of the sociopolitical and religious context in which the passage of Gn 2,4b-25 was formed, which prepares for an understanding of the anthropology underlying the text under study. This anthropology is characterized by presenting the human being, man and woman, in relation to each other, with created things and with God.